Effect of Digital Marketing and Customer Relationship Marketing on Consumer Satisfaction and Consumer Loyalty at Gypsy Belles Jewelry Bali - Luh Komang Candra Dewi; Ayunita Sindya Dewi; Dewiwati Sujadi (Budapest International Research and Critics University, 2022)
Online marketing has become a mandatory activity that needs to be done by all business people. And in order to get maximum results regarding the application of digital marketing, they do not hesitate to use several digital marketing service providers. Of course, it is not without reason that they chose a digital agency. They must do that because not all business actors are able to implement the most appropriate marketing strategy for the development of their products and brands. The development of the digital business world has been quite rapid, but there are still many business actors who need a person, institution, or company who is able to meet their needs regarding the use of digital marketing. This study aims to analyze effect of digital marketing and customer relationship marketing on consumer satisfaction and consumer loyalty at Gypsy Belles Jewelry Bali. This research uses quantitative analysis. The population in this study are consumers who buy at Gypsy Belles Jewelry Bali. This study uses 19 statements so that the sample studied is a minimum of 95 respondents and a maximum of 190 respondents. Hypothesis testing is carried out using the WarpPLS inferential analysis tool. The results show that digital marketing has a positive and significant effect on consumer satisfaction. Customer relationship marketing has a positive and significant effect on consumer satisfaction. Digital marketing has a positive and significant effect on consumer loyalty. Customer relationship marketing has a positive and not significant effect on consumer loyalty. Consumer satisfaction has a positive and significant effect on consumer loyalty.